Morphometric analysis of fibrovascular pigment epithelial detachments treated with ranibizumab and aflibercept. Issue 1 (January 2022) - Karampelas, Michael; Syriga, Maria; Petrou, Petros; Georgalas, Ilias; Papaconstantinou, Dimitrios; Brouzas, Dimitrios
Purpose: To assess fibrovascular pigment epithelial detachments (PED) and their response to two different anti-VEGF agents using optical coherence tomography (OCT) morphometric analysis. Methods: Seventy-three consecutive, treatment-naïve eyes with fibrovascular PED (>125 μm) treated with ranibizumab or aflibercept were retrospectively included. A custom-made software was used to manually segment and calculate PED maximum height, base area, volume and internal reflectivity at baseline, after three injections and 1 year. Results: Visual acuity (VA) change was 2 ETDRS letters ± 7.6 after three injections and 3.2 ETDRS letters ± 10.3 at 1 year. There was no significant difference between VA changes amongst the two drugs. At 1 year, anti-VEGF treatment resulted in a mean reduction of 125 μm in maximum PED height, of 2.26 mm 2 in base area and of 0.54 mm 3 in volume with a corresponding increase in reflectivity. These changes were more prominent in the aflilbercept group. The observed PED and VA changes at year 1 were strongly correlated with their values at baseline and after three injections. Conclusions: Anti-VEGF treatment resulted in a reduction of all PED dimensions and a corresponding increase in optical reflectivity. Higher, larger and more hypo-reflective PEDs demonstrated a better anatomical response, especially with aflibercept, but this was not correlated with VA.